1984
DOI: 10.1016/0092-8674(84)90196-x
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection of actin-binding proteins and actin antibodies demonstrates involvement of nuclear actin in transcription of lampbrush chromosomes

Abstract: SummaryNuclei of amphibian oocytes contain large amounts of actin, mostly in unpolymerized or short-polymer form. When antibodies to actin or actin-binding proteins (fragmin and the actin modulator from mammalian smooth muscle) are injected into nuclei of living oocytes of Pleurodeles waltlii, transcription of the lampbrush chromosomes, but not of the rRNA genes, is inhibited. When transcription is repressed by drugs or RNA is digested by microinjection of RNAase into oocyte nuclei, an extensive meshwork of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
157
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(167 citation statements)
references
References 65 publications
10
157
0
Order By: Relevance
“…In their experiments, Triturus oocytes, still in the ovary, regained their normal structure 1-2 d after removal of the inhibitor. Later studies by Scheer and his colleagues (Scheer, 1987;Scheer et al, 1984) showed that isolated oocytes could also recover from the effects of actinomycin when incubated 1-2 d in a medium without the inhibitor. Similarly, lampbrush chromosomes can recover their normal structure after y-ray treatment (Loones, 1979) or after heat shock, either in vitro (Flannery and Hill, 1988) or in vivo (Rodriguez-Martin et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In their experiments, Triturus oocytes, still in the ovary, regained their normal structure 1-2 d after removal of the inhibitor. Later studies by Scheer and his colleagues (Scheer, 1987;Scheer et al, 1984) showed that isolated oocytes could also recover from the effects of actinomycin when incubated 1-2 d in a medium without the inhibitor. Similarly, lampbrush chromosomes can recover their normal structure after y-ray treatment (Loones, 1979) or after heat shock, either in vitro (Flannery and Hill, 1988) or in vivo (Rodriguez-Martin et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ␤-actin in the nucleus was documented for the first time many years ago (Egly et al, 1984;Scheer et al, 1984), but the connection between ␤-actin and gene transcription has only recently been demonstrated (Olave et al, 2002;Pederson and Aebi, 2002;Fomproix and Percipalle, 2004;Grummt, 2006;Jockusch et al, 2006;Percipalle and Visa, 2006;Obrdlik et al, 2007). Nuclear ␤-actin associates with components of the ATP-dependent chromatin-remodeling complexes (Olave et al, 2002;Bettinger et al, 2004), with RNP particles (Percipalle and Visa, 2006), and with the three RNA polymerases in the eukaryotic cell nucleus, both in vitro and in vivo (Hu et al, 2004;Philimonenko et al, 2004;Kukalev et al, 2005;Wu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A ctin and myosin I are present not only in the cytoplasm but also in the cell nucleus (1,2), where they have been implicated in transcription of protein-coding genes (3)(4)(5) and nuclear export (6). Many other cytoskeletal components have also been found in the cell nucleus, and some of them have been tentatively implicated in gene expression (reviewed in ref.…”
mentioning
confidence: 99%